Human–AI Collaboration in EFL Writing: A Conceptual Framework for Intelligent Feedback Systems - Vini Rizki Nurodiah; Titin Nurjanah; Andang Saehu; Cipto Wardoyo (Ma'soem University, 2026)
Artificial intelligence (AI) has increasingly been integrated into English as a Foreign Language (EFL) writing instruction, offering new opportunities to improve students’ writing through automated and intelligent feedback. Nevertheless, existing studies remain fragmented and predominantly emphasize the technological capabilities of AI tools rather than their pedagogical integration within classroom practice. This study aims to synthesize recent literature and propose a conceptual framework for human–AI collaboration in EFL writing by integrating technological, pedagogical, and learner-centered perspectives. Employing a qualitative library research design, the study systematically reviewed peer-reviewed journal articles published between 2016 and 2026. Data were collected from Google Scholar, Scopus, ERIC, and ScienceDirect and analyzed using thematic analysis involving coding, categorization, and theme development. The findings reveal three interrelated components of effective AI-assisted writing instruction: AI as an intelligent feedback provider, teachers as pedagogical scaffolding agents, and students as self-regulated learners. These components interact dynamically to support writing development, strengthen learner autonomy, and promote meaningful engagement with feedback. The review also identifies several pedagogical challenges, including learners’ overdependence on AI-generated feedback and limited critical engagement with automated suggestions. The study concludes that effective AI integration in EFL writing requires a balanced collaboration between technological support and pedagogical guidance, grounded in constructivist learning theory, self-regulated learning, and feedback literacy. The proposed conceptual framework contributes to the theoretical foundation of AI-assisted language learning and provides practical implications for integrating intelligent feedback systems into EFL writing instruction.